ChemInform Abstract: Amine‐Borane Mediated Metal‐Free Hydrogen Activation and Catalytic Hydrogenation. Issue 41 (7th October 2014) - Sumerin, Victor; Chernichenko, Konstantin; Schulz, Felix; Lesleka, Markku; Rieger, Bernhard; Repo, Timo
Abstract Review: 82 refs.